2009
DOI: 10.1097/mpg.0b013e3181919695
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Care in Pediatric Crohn Disease

Abstract: There is variation in diagnostic and therapeutic interventions in the management of pediatric Crohn disease, and gaps exist between recommended and actual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…In an examination of 65 adult patients with confirmed IBD, Reddy et al 12 found that there was suboptimal dosing of maintenance medications, prolonged use of corticosteroids, failure to use steroid-sparing agents, and inadequate attention to metabolic bone disease and screening for colorectal cancer. Colletti et al 13 found similar results in a study of 246 pediatric patients with CD. They noted variation in diagnostic interventions, including stool tests for pathogens, imaging of the small intestine, measurement of thiopurine methyltransferase before starting treatment with a thiopurine, and testing for tuberculosis before starting treatment with infliximab.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…In an examination of 65 adult patients with confirmed IBD, Reddy et al 12 found that there was suboptimal dosing of maintenance medications, prolonged use of corticosteroids, failure to use steroid-sparing agents, and inadequate attention to metabolic bone disease and screening for colorectal cancer. Colletti et al 13 found similar results in a study of 246 pediatric patients with CD. They noted variation in diagnostic interventions, including stool tests for pathogens, imaging of the small intestine, measurement of thiopurine methyltransferase before starting treatment with a thiopurine, and testing for tuberculosis before starting treatment with infliximab.…”
supporting
confidence: 68%
“…With the participation of 93 pediatric gastroenterologists at 48 practice sites, the study was completed in 2008 and the findings published in 2009. 13 At the end of the 2-year grant, the cohort study had been undertaken and the design completed for the improvement network. The components of the network are described below.…”
Section: History Of Improvecarenowmentioning
confidence: 99%
“…A multicenter pediatric study of 246 children with IBD from 48 practices who were initiating thiopurine and/or infliximab therapy demonstrated that 29% were not tested for stool pathogens at the time of initial IBD diagnosis, 30% did not receive a skin test and/or chest radiograph to screen for tuberculosis prior to infliximab initiation, and 31% of those with normal thiopurine methyltransferase (TPMT) status did not receive a starting dose of 6-mercaptopurine (6-MP) between 1 and 1.5 mg/kg/day. 8 Further evidence of a gap in IBD quality comes from a retrospective study of 67 adult IBD patients referred to a tertiary care center. Sixty-four percent were inadequately dosed with 5-aminosalicylate (5-ASA) medications, 60% receiving chronic steroids had not initiated steroid-sparing medications, and 82% of patients treated with immunomodulators received suboptimal dosages.…”
Section: Quality Of Care: Implications For Inflammatory Bowel Diseasementioning
confidence: 99%
“…Importantly, TPMT genotype is a strong predictor for TPMT activity and even patients heterozygous for the TPMT loss-of-function alleles *2A or *3 showed significantly higher incidences of dose reductions due to toxicity [67,68]. Due to the substantial body of evidence that links TPMT genotype to thiopurine treatment outcomes and adverse events, TPMT genotyping is already widely applied in clinical practice [69,70]. The costeffectiveness of preemptive TPMT genotyping remains however inconclusive [71,72] and data from randomized controlled trials is currently lacking.…”
Section: Associations Between Tpmt Genotype and Thiopurine Toxicitymentioning
confidence: 99%